Systemic inhibition of tissue-nonspecific alkaline phosphatase alters the brain-immune axis in experimental sepsis - Brichacek, Allison L. (Sci Rep, 2019)
Tissue-nonspecific alkaline phosphatase (TNAP) is a ubiquitous enzyme present in many cells and tissues, including the central nervous system. Yet its functions at the brain-immune axis remain unclear. The goal of this study was to use a novel small molecular inhibitor of TNAP, SBI-425, to interrogate the function of TNAP in neuroimmune disorders. Following intraperitoneal (IP) administration of SBI-425, mass spectrometry analysis revealed that the SBI-425 does not cross the blood-brain barrier (BBB) in healthy mice. To elucidate the role of TNAP at the brain-immune axis, mice were subjected to experimental sepsis and received either vehicle or SBI-425 (25 mg/kg, IP) daily for 7 days. While SBI-425 administration did not affect clinical severity outcomes, we found that SBI-425 administration suppressed CD4 + Foxp3+ CD25− and CD8 + Foxp3+ CD25− splenocyte T-cell populations compared to controls. Further evaluation of SBI-425’s effects in the brain revealed that TNAP activity was suppressed in the brain parenchyma of SBI-425-treated mice compared to controls. When primary brain endothelial cells were treated with a proinflammatory stimulus the addition of SBI-425 treatment potentiated the loss of barrier function in BBB endothelial cells. To further demonstrate a protective role for TNAP at endothelial barriers within this axis, transgenic mice with a conditional overexpression of TNAP were subjected to experimental sepsis and found to have increased survival and decreased clinical severity scores compared to controls. Taken together, these results demonstrate a novel role for TNAP activity in shaping the dynamic interactions within the brain-immune axis.